Statistical Inference for the Parameter of Pareto Distribution Based on Progressively Type-I Interval Censored Sample (Communications in Mathematical Research, 2021)
In this paper, the estimation of parameters based on a progressively type-I interval censored sample from a Pareto distribution is studied. Different methodsof estimation are discussed, which include mid-point approximation estimator, themaximum likelihood estimator and moment estimator. The estimation proceduresare discussed in details and compared via Monte Carlo simulations in terms of theirbiases.